Classification and Milling Increase Fly Ash Pozzolanic Reactivity - Snellings, Ruben; Kazemi-Kamyab, Hadi; Nielsen, Peter; Van den Abeele, Liesbet (Frontiers in Built Environment, 2021)
Upcycling and reclaiming of low quality or stored coal combustion fly ashes could enable to tap into a voluminous resource of supplementary cementitious materials (SCMs) for low-carbon blended cements. Low reactivity fly ashes are usually either too crystalline or too coarse. Beneficiation treatments for coarse fly ashes comprise size classification or milling processes to extract or produce fine size fractions of higher pozzolanic reactivity. This article compares the effect of size classification and milling treatments on the reactivity of a siliceous fly ash (FA). The intrinsic chemical reactivity is assessed using the R3 heat release test method. The results showed significant increases of 57 and 40% for fine classified and milled fly ash compared to the initial fly ash, respectively. In addition heat release and portlandite consumption were measured for blended cements with 30 wt.% Portland cement replacement by the fly ashes. Both test results are combined to calculate the degree of reaction of the fly ashes over time in blended cement. The results demonstrate a strong effect of particle size on fly ash reactivity and degree of reaction. It is shown that increasing the inherent reactivity of fly ashes is an effective way of both accelerating compressive strength gain and enhancing late age strength with fine classified fly ashes reaching equivalent strength as neat Portland cement by 28 days and attaining a strength activity index of 137% by 90 days.